Coping With COVID-19: Mindfulness-Based Approaches for Mitigating Mental Health Crisis - Antonova, Elena; Schlosser, Karoly; Pandey, Rakesh; Kumari, Veena (Frontiers in Psychiatry, 2021)
The novel coronavirus disease COVID-19 has already impacted a significant proportion of the world population. Governments of many countries have imposed social distancing measures to mitigate the spread of the SARS-Cov-2 virus causing the COVID-19 disease. The direct impact of COVID-19 on those with clinical presentation, their families and the health care workers, as well as the impact of the mitigation measures on the rest of the population is threatening to result in a global mental health pandemic, including anxiety, depression, panic attacks, post-traumatic stress symptoms, psychosis, addiction, obsessive-compulsive disorder, and suicidality. These mental health effects will be present both acutely and long after the pandemic is over. A global effort is called for in dealing with an imminent global mental health pandemic secondary to COVID-19 itself by establishing appropriate evidence-based guidelines and coordinating service provision to address the risk of emergence of new as well as the exacerbation of the existing mental health issues. The global context also provides an extraordinary opportunity for studying the factors and mechanisms underlying individual differences in response to and resilience in the face of an unprecedented challenge to one’s ‘normal’ way of life in the context of physical and psychological threat and long-term uncertainty. We outline the particular suitability of mindfulness-based approaches to the prevention and management of mental health issues, as well as for the promotion of well-being and adaptability in the face of long-term uncertainty and profound changes, individual and societal, as this pandemic continues to unfold.